Strategies of Regional Levies of the Agriculture and Plantation Office of Central Java Province - Diah Setyorini Gunawan; Icuk Rangga Bawono (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2023)
The management of regional levies at the Regional Apparatus Organizations needs to be done optimally, including in this case the management of regional levies at the Agriculture and Plantation Office of Central Java Province. In this regard, it is necessary to prepare a Local Own-Source Revenue strategies from the regional levies sector. The preparation of the strategies based on the results of the identification of strengths, weaknesses, opportunities, and threats in terms of collecting regional levies. This study used primary data and secondary data. Primary data include the interviews results with key informants regarding the strengths, weaknesses, opportunities, and threats in terms of collecting regional levies while secondary data include data on regional levies and references related to the Agriculture and Plantation Office of Central Java Province. This study used SWOT analysis. From this study, it can be identified the strengths, weaknesses, opportunities, and threats in terms of collecting regional levies and the strategies for the regional levies at the Agriculture and Plantation Office of Central Java Province Keywords: Strategies, Local Own-Source Revenue, Regional Levies.